(untitled) (Proceeding of SINERGY, 2026)
Plastic waste is a major environmental problem in Indonesia due to its large volume, long decomposition time, and low management rate. Bank Sampah Wonorejo provides a plastic waste pickup service to support recycling activities; however, the use of manual data recording has caused inefficiencies and increased the risk of data loss. This study aims to develop a web-based information system called PLASTICARE to support integrated management of plastic waste pickup activities. PLASTICARE was developed using the Waterfall method within the System Development Life Cycle (SDLC), which includes communication, planning, modelling, construction, and deployment stages. Data were collected through interviews and literature studies, while system design employed Unified Modeling Language (UML) such as use case diagram and activity diagram. The system was implemented using HTML, CSS, and PHP. The resulting system features plastic waste pickup submission, administrative approval, reporting, graphical visualization of daily plastic waste weight, and report downloads in PDF format. PLASTICARE improves efficiency, data accuracy, and transparency in waste management processes. The system is expected to increase community participation in plastic waste recycling and support sustainable environmental management